CAPITAL INVESTMENT: A CASE STUDY OF ACEH PROVINCE, INDONESIA - Abdul Hakim; Gemala Dewi (Universitas Syiah Kuala, 2022)
The capital investment in Aceh between 2010 and 2017 happens after the conflict and tsunami. Management of capital investment, its growth, and factors inhibiting capital investment after conflict and disaster are the focal points of this study. The purpose of this research is to determine how foreign investors in Aceh are protected under Law Number 25, 2007 and what types of security factors are present in Aceh. This research consisted of normative legal or library research. As normative legal research, only secondary data, which includes primary, secondary, and tertiary legal materials, were utilized. Based on the analysis, the Province of Aceh's management capital investment consisted of management governed by legislation governing Aceh's governance and legislation governing capital investment. In addition, the regional government of Aceh stipulated legislation governing capital investments. The growth of capital investment, both domestic and foreign, exhibited an increase, although it was not statistically significant. This slow growth was caused by security insurance, inadequate infrastructure, and the lack of legal certainty in conflict, earthquake, and tsunami-affected regions.